(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
he main focus of this paper is the process of the formation of communal lands in a selected area as part of the formation and construction of the postrevolutionary state. In this sense, it seeks to retrieve a signiicant part of the local history, the speeches and examples of peasant leadership of the municipality of Tanlajas, encompassing them in a major historical context. Furthermore, the present contribution aims at combining oral history and the documented history available in the Historic Archives of the National Agrarian Oice of San Luís Potosí with ield evidence, especially by elaborating original cartography on forms of land ownership until 1920 in a gis format, in order to study the processes of the agrarian reform. he use of the gis tools has allowed a novel insight into the interpretation of the maps available in the agrarian records, and it has led to a better present-day geographic localization of the historical forms of land ownership.